Kinetic modeling of Dodonaea viscosa decomposition under microwave-assisted pyrolysis: A combined model-fitting and iso conversional approach - Shakir, Safa W.; Al-Yaqoobi, Atheer M. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
This work examines the kinetic behavior of Dodonaea viscosa during microwave-assisted pyrolysis as a means of addressing the limited insight regarding how biomass degradation pathways are affected by non-conventional heating. Thermogravimetric data were analyzed using both model-fitting (Coats–Redfern) and model-free (Friedman and Kissinger–Akahira–Sunose) methods to provide a thorough analysis. Results indicated that a third-order kinetic model appropriately described the general trend of decomposition; in contrast, iso-conversional analyses verified a multi-stage sequence with the activation energy declining during volatile yields and increasing at elevated conversion levels as a result of carbonaceous residue decomposition. These complementary understandings demonstrate that microwave-assisted heating ensures the development of characteristic reaction dynamics rather than those derived from traditional pyrolysis and thus supply mechanistic support for increased energy efficiency. The results not only unify methodology gaps between model-fitting and iso-conversional methodology but also provide useful direction for the optimization of microwave pyrolysis parameters, thus enhancing the sustainable production of lignocellulosic biomass-derived bioenergy.